2018
DOI: 10.3390/publications6040048
|View full text |Cite
|
Sign up to set email alerts
|

Research Support Services in Spanish Academic Libraries: An Analysis of Their Strategic Plans and of an Opinion Survey Administered to Their Directors

Abstract: The transition from print to digital information has transformed the role of academic libraries, which have had to redefine themselves as intermediaries and partners in the learning and research processes. This study analyzes the evolution and current provision of research support services in Spanish academic libraries through an analysis of the three strategic plans published by the Spanish association of academic libraries (REBIUN) and a survey administered to the library directors. Results show that academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…The limited resources faced by the academic library in providing research support services is an issue that emerged from three of the experts. This is in line with several previous studies stating that limited resources in terms of staff, budget, and equipment are an obstacle faced by academic libraries in research support services (Borrego and Anglada 2018). One study found that Italian scientific institutions and universities lack strong investments in human resources and infrastructures (Rubbia et al 2014).…”
Section: Limited Resourcessupporting
confidence: 88%
See 2 more Smart Citations
“…The limited resources faced by the academic library in providing research support services is an issue that emerged from three of the experts. This is in line with several previous studies stating that limited resources in terms of staff, budget, and equipment are an obstacle faced by academic libraries in research support services (Borrego and Anglada 2018). One study found that Italian scientific institutions and universities lack strong investments in human resources and infrastructures (Rubbia et al 2014).…”
Section: Limited Resourcessupporting
confidence: 88%
“…In research support services, librarians have a new role as intermediaries and partners in the learning and research processes (Borrego and Anglada 2018). The role of librarians as partners is referred to as subject-based information experts (Sheridan Brown and Swan 2007;Revez 2018).…”
Section: Improvement Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Library services support research and learning, promote literacy, and enrich the cultural and intellectual life of the community [91,92]. Library services are diverse and aim to provide quality standards and efficient delivery of information to support learning and research goals [93,94]. This parameter is characterized by various dimensions of library services.…”
Section: Library Servicesmentioning
confidence: 99%